Indigenous and Minority Placenames Australian and International Perspectives - D. Clark, Ian; Hercus, Luise; Kostanski, Laura (ANU Press, 2014)
This book showcases current research into Indigenous and minority placenames in Australia and internationally. Many of the chapters in this volume originated as papers at a Trends in Toponymy conference hosted by the University of Ballarat in 2007 that featured Australian and international speakers. The chapters in this volume provide insight into the quality of toponymic research that is being undertaken in Australia and in countries such as Canada, Finland, South Africa, New Zealand, and Norway. The research presented here draws on the disciplines of linguistics, geography, history, and anthropology. The book includes meticulous studies of placenames in central NSW and the Upper Hunter region; Gundungurra cave names; western Arnhem Land; Northern Cape York Peninsula and Mount Wheeler in Queensland; saltwater placenames around Mer in the Torres Strait; and the Kaurna in South Australia.